Pastoral, Bukan Spekulatif: Resepsi Historis-Teologis Martin Luther atas Predestinasi: Pastoral, Not Speculative: Martin Luther’s Historical-Theological Reception of Predestination - Bona Ventro Simatupang (RERUM: Journal of Biblical Practice, 2026)
AbstractThe doctrine of predestination is often trapped in speculative misconceptions that reduce its depth to merely a Calvinist theological framework. This article aims to critically analyze the concept of predestination in the theology of Martin Luther and to trace the patterns of its reception and reinterpretation within the Calvinist tradition, the English Reformation, and Lutheran churches in Indonesia, with particular focus on Huria Kristen Batak Protestan (HKBP). Using a historical-theological method through literature study, this research demonstrates that, for Luther, predestination is not a rigid deterministic doctrine, but rather a logical consequence of the teaching of justification by faith and the radicality of God’s grace (Sola Gratia). The findings reveal significant differentiation in its reception: the Calvinist tradition develops it in a systematic-dogmatic manner, whereas Lutheran churches, including HKBP, position it as a source of consolation for the anxious soul. The primary contribution of this study is to reaffirm Luther’s predestination as a contextual pastoral theological category, while distinguishing it from the more normative and speculative doctrinal formulations within its recipient traditions. This study concludes that predestination, from a Lutheran perspective, functions as an anchor of assurance of faith, affirming that salvation is entirely secure in the hands of the faithful God, rather than in the fragility of human will.     AbstrakDoktrin predestinasi sering kali terjebak dalam miskonsepsi spekulatif yang mereduksi kedalamannya hanya pada kerangka teologi Calvinis. Artikel ini bertujuan untuk menganalisis secara kritis konsep predestinasi dalam teologi Martin Luther serta menelusuri pola penerimaan dan reinterpretasinya dalam tradisi Calvinis, Reformasi Inggris, dan gereja Lutheran di Indonesia, dengan fokus pada Huria Kristen Batak Protestan (HKBP). Menggunakan metode historis-teologis melalui studi kepustakaan, penelitian ini menunjukkan bahwa predestinasi bagi Luther bukanlah doktrin deterministik yang kaku, melainkan konsekuensi logis dari ajaran pembenaran oleh iman dan radikalitas anugerah Allah (Sola Gratia). Hasil penelitian mengungkapkan adanya diferensiasi signifikan dalam resepsinya: tradisi Calvinis mengembangkannya secara sistematis-dogmatis, sementara gereja-gereja Lutheran, termasuk HKBP, menempatkannya sebagai sumber penghiburan bagi jiwa yang gelisah. Kontribusi utama penelitian ini adalah menegaskan kembali predestinasi Luther sebagai kategori teologis pastoral yang kontekstual, sekaligus membedakannya dari perumusan doktrin yang lebih normatif dan spekulatif dalam tradisi-tradisi reseptornya. Penelitian ini menyimpulkan bahwa predestinasi dalam perspektif Lutheran merupakan jangkar kepastian iman yang memastikan keselamatan sepenuhnya aman di tangan Allah yang setia, bukan dalam rapuhnya kehendak manusia.